2017
DOI: 10.3389/fpsyg.2017.00714
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Dispositions Toward Ridicule and Laughter in the Workplace: Adapting and Validating the PhoPhiKat-9 Questionnaire

Abstract: The current paper addresses the measurement of three dispositions toward ridicule and laughter; i.e., gelotophobia (the fear of being laughed at), gelotophilia (the joy of being laughed at), and katagelasticism (the joy of laughing at others). These traits explain inter-individual differences in responses to humor, laughter, and social situations related to humorous encounters. First, an ultra-short form of the PhoPhiKat-45 (Ruch and Proyer, 2009) was adapted in two independent samples (Construction Sample N =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 19 publications
6
23
0
Order By: Relevance
“…Firstly, due to the low prevalence of gelotophobes in non-clinical population, the sample sizes were relatively small. However, both the number of participants selected and the strategy adopted for recruiting them (i.e., construction of extreme groups) were in the line with previous research concerning gelotophobia ( Papousek et al, 2014 ; Ruch et al, 2015 ). Lastly, it is important to indicate that some particular laughter (or humor)-related aspects were not included in these studies.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Firstly, due to the low prevalence of gelotophobes in non-clinical population, the sample sizes were relatively small. However, both the number of participants selected and the strategy adopted for recruiting them (i.e., construction of extreme groups) were in the line with previous research concerning gelotophobia ( Papousek et al, 2014 ; Ruch et al, 2015 ). Lastly, it is important to indicate that some particular laughter (or humor)-related aspects were not included in these studies.…”
Section: Discussionsupporting
confidence: 63%
“…The results revealed that individuals with gelotophobia did not show a reduced emotional induction to positive emotions compared with non-gelotophobes; interestingly, however, they showed a higher degree of affective induction to negative emotions, that is, high scores of subjective anxiety or sadness after watching anxiety- or sadness-causing films, respectively. In line with the analysis of gelotophobes’ reactions concerning the affective states of others, Ruch et al (2015) used the Facial Action Coding System to analyze the potential differences between gelotophobes and non-gelotophobes in joy and contempt responses to videos of laughter-eliciting emotions (e.g., amusement or relief). In particular, they found that gelotophobes exhibited reduced facial expressions of joy (i.e., joyful smiles) and more expressions of contempt when they were exposed to laughter-eliciting emotions.…”
Section: Introductionmentioning
confidence: 99%
“…Heightened expressions of katagelasticism have been linked with bullying‐type behaviors (already in young children and in adolescents; Proyer, Neukom, Platt & Ruch, ) and with psychopathic personality traits (Proyer, Flisch, Tschupp, Platt & Ruch, ). Like gelotophiles, katagelasticists exhibit low self‐control (Chiu et al ., ), but higher levels of work stress (Hofmann et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, despite a certain degree of common variance between these two dispositions, they can predict independent psychological outcomes (e.g., relationship satisfaction; Brauer & Proyer, ). Gelotophiles are likelier to use self‐presentation styles aimed at gaining social approval (Renner & Heydasch, ), have a lowered capacity of self‐control (Chiu, Hsu, Lin, Chen & Liu, ), and report higher subjective levels of both personal and occupational satisfaction (e.g., Hofmann, Ruch, Proyer, Platt & Gander, ).…”
Section: Introductionmentioning
confidence: 99%
“…Research on personality and humor demonstrates that people habitually differ in the way they cognitively evaluate humorous stimuli ( Ruch and Hehl, 2007 ), use and communicate humor in everyday life ( Craik et al, 1996 ; Fox et al, 2016 ), and emotionally respond to humor ( Ruch, 2007 ; Platt et al, 2013 ; Ruch et al, 2015 ). The predominant emotional reaction to humor was labeled exhilaration 3 (or amusement), which in classifications of emotions is defined as a facet of joy ( Ruch, 1993 ).…”
Section: Introductionmentioning
confidence: 99%